Australia antigen and primary biliary cirrhosis - MacSween, R. N. M. (1973)
Sera from 64 patients with primary biliary cirrhosis have been examined for Australia antigen (Au). On immunodiffusion and immunoelectrophoresis all sera were negative. Using a radioimmunoprecipitation technique 15·6% of sera contained antigen compared with an incidence of 3·1% in matched controls, a significant difference (p = 0·015). Anti-Au was found in 9·4% of patients and in 7·8% of controls. In lymphocyte transformation studies lymphocytes from one of 24 patients with primary biliary cirrhosis transformed on stimulation with an Au-rich serum.